Effects of fuel input on coherent jet length at various ambient temperatures. (5th May 2019) - Tang, Guangwu; Chen, Yuchao; Silaen, Armin K.; Krotov, Yury; Riley, Michael F.; Zhou, Chenn Q.
Highlights: A comprehensive coherent jet CFD model has been developed for the electric arc furnace process. A modified k-epsilon turbulence model was used to model the turbulence mixing. The CFD model has been validated with experimental data. The effects of fuel input on the coherent jet length have been investigated. Abstract: The electric arc furnace (EAF) is used to produce steel, primarily from scrap, using electricity and chemical energy. Typically, the EAF process consists of two stages: melting and refining. During the refining stage, high speed coherent gas jets are used to increase the depth of oxygen jet penetration for a better stirring of the liquid steel and to promote decarburization reactions. A coherent jet is defined when the supersonic gas jet is shrouded by a flame envelope, which leads to a higher potential core length (the length up to which the axial jet velocity equals the exit velocity at the nozzle). In this paper, a coherent jet computational fluid dynamics (CFD) model is developed with detailed consideration of compressible gas flow properties and oxy-fuel combustion effects. The model is validated by comparing the coherent jet axial velocity profiles with experimental measurements. The developed CFD model was used to investigate (1) the effect of ambient temperature on the coherent jet potential core length, and (2) at high-temperature steelmaking conditions, the effects of fuel composition on the coherent jet potential core length. The results indicate that the coherent jet potential core length increases with the ambient temperature in the range of 300–1922 K. At high-temperature steelmaking conditions, when the fuel input exceeds 6.5% of the primary oxygen volume flow rate, the potential core length of the coherent jet will not increase significantly. Three different types of fuel, blast furnace gas, natural gas, and coke oven gas were used to shroud a coherent jet, and the results indicate that a lower shrouding fuel molecular weight or gas density will increase coherent jet potential core length. This validated CFD model can be used to investigate the effects of burner operation parameters on coherent jet properties for industrial EAFs.